Influence of Pore Size on the Optical and Electrical Properties of Screen Printed TiO2 Thin Films - Dinfa Luka Domtau; Justus Simiyu; Elijah Omollo Ayieta; Godwin Mwebeze Asiimwe; Julius Mwakondo Mwabora (Advances in Materials Science and Engineering)
Influence of pore size on the optical and electrical properties of TiO2 thin films was studied. TiO2 thin films with different weight percentages (wt%) of carbon black were deposited by screen printing method on fluorine doped tin oxide (FTO) coated on glass substrate. Carbon black decomposed on annealing and artificial pores were created in the films. All the films were 3.2 µm thick as measured by a surface profiler. UV-VIS-NIR spectrophotometer was used to study transmittance and reflectance spectra of the films in the photon wavelength of 300–900 nm while absorbance was studied in the range of 350–900 nm. Band gaps and refractive index of the films were studied using the spectra. Reflectance, absorbance, and refractive index were found to increase with concentrations of carbon black. There was no significant variation in band gaps of films with change in carbon black concentrations. Transmittance reduced as the concentration of carbon black in TiO2 increased (i.e., increase in pore size). Currents and voltages (I-V) characteristics of the films were measured by a 4-point probe. Resistivity (ρ) and conductivity (σ) of the films were computed from the I-V values. It was observed that resistivity increased with carbon black concentrations while conductivity decreased as the pore size of the films increased.